Two-Year Survival of High-Viscosity Glass Ionomer in Children with Molar Incisor Hypomineralization - DURMUŞ, BAŞAK; KARGÜL, BETÜL; BEKİROĞLU, GÜLNAZ NURAL (KARGER, 2020)
Objective: We assessed the clinical survival of a high-viscosity glass ionomer (HVGI) at the 2-year follow-up to restore molar incisors severely affected by hypomineralization after selective carious tissue removal (SCR). The null hypothesis tested was that there are no differences in the overall survival times in the categories of the variables of interest. Methods: A total of 134 fully erupted first molar incisors with hypomineralization, cavitated and with moderate-to-deep carious lesions without hypersensitivity or pain (MIH treatment need index 2a-c), were included in the study. HVGI (Equia Forte (R); GC, Tokyo, Japan) restorations were applied after SCR to soft carious dentin. The follow-up lasted 2 years. The end point was defined as the absence of endodontic and restorative complications. Two-year, and 18-, 12-, and 6-month survival probabilities and standard errors were calculated using the Kaplan-Meier method. Survival probabilities according to patient gender, jaw, and lesion severity groups were compared using the log-rank test. Restorations were evaluated using the modified US Public Health Service criteria. Results: HVGI restorations showed cumulative survival probabilities of 95.5% at 6 months, 94% at 12 months, 87.5% at 18 months, and 87.5% at 24 months. Survival probabilities according to patient gender, jaw, and lesion severity groups were not statistically significantly different (p > 0.05). Therefore, the null hypothesis was accepted. Conclusion: Following SCR, HVGI restoration provided moderate survival probabilities, suggesting that the SCR technique is effective.
Keywords: Molar incisor hypomineralization; Survival probabilities; High-viscosity glass ionomer; Selective carious tissue removal; COMPOSITE RESIN RESTORATIONS; CARIES REMOVAL; CLINICAL-PERFORMANCE; COMPLETE EXCAVATION; TRIAL; MIH; HEALTH; TEETH